National Wrestling Sports Characteristics of the Relationships Between Coaches and Athletes (Eurasian Research Bulletin, 2023)
As the symbol of nobility and courage of wrestling is inculcated in the minds of students, first of all, attention is paid to the pedagogical significance of the sport of wrestling. First of all, in order to make an exemplary assessment of the precompetition condition of an athlete engaged in the sport of wrestling, it is necessary to monitor his psychological, both pedagogical and practical processes. The article also examines the characteristics of the pre-start relationship between coaches and athletes in the national sport of wrestling